Form of Bundengan Traditional Music Arrangement by Sanggar Akustika in Wonosobo (Jurnal Seni Musik, 2023)
Bundengan is one of the traditional musical instruments in Indonesia that originates and developes in Wonosobo Regency, Central Java. The bundengan music group Akustika provides arrangements for bundengan music. This research aims to determine and provide a description of the form of bundengan music arrangement by the bundengan music group Akustika. The method used in this research was qualitative with a musicological approach. Data collection was carried out through observation, interviews, and documentation techniques. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The research results show that the musical arrangement of Bundengan in Sanggar Akustika, Wonosobo Regency, combines traditional Bundengan musical instruments with instruments such as cak, guitar, keyboard, violin, bass, and drums. The performed music genres include modern pop, campursari, dangdut, nostalgic songs, and regional songs in Indonesia. The basic tones used are C major and G major, with mixed arrangement styles. During the performance, each musical instrument utilizes a limited repetitive playing pattern until the completion of the song. All the instruments in the Bundengan music complement each other and form dynamic and harmonious musical patterns.